Neuropsychiatric symptoms in patients with dementia and the longitudinal costs of informal care in the Cache County population - Gail B. Rattinger; Chelsea L. Sanders; Elizabeth Vernon; Sarah Schwartz; Stephanie Behrens; Constantine G. Lyketsos; JoAnn T. Tschanz (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Severity of dementia and neuropsychiatric symptoms contribute to increasing informal care costs. We examined which neuropsychiatric symptoms subdomains (NPS‐SD) were associated with informal costs in a population‐based sample. Methods Dementia progression and informal costs (2015 dollars) were estimated from the Cache County Dementia Progression Study. Overall NPS and specific NPS‐SD were assessed with the Neuropsychiatric Inventory. Generalized Estimating Equations (GEE with gamma‐distribution/log‐link) modeled the relationship between NPS‐SDs and informal cost trajectories. Results Two hundred eighty participants (52.1% female; age M = 85.67, SD = 5.60) exhibited an adjusted cost increase of 5.6% (P = .005), 6.4% (P < .001), 7.6% (P = .030), and 13% (P = .024) for every increasing Neuropsychiatric Inventory unit in psychosis‐SD, affective‐SD, agitation/aggression‐SD, and apathy‐SD, respectively. An increase in each unit of apathy was associated with a 2% annual decrease in costs (P = .040). Discussion We extend our prior work on informal costs and dementia severity by identifying NPS‐SD associated with informal costs. Interventions targeting NPS‐SD may lower informal costs.